Keunggulan Bersaing dan Penciptaan Nilai pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sri Rani Fauziah; I Made Sudana (Jurnal Manajemen dan Bisnis Indonesia, 2013)
Resources, capabilities and core competencies are the basic characteristics of the competitive advantage. How resources and capabilities for the long time can contribute to creating value to the company and be able to compete in the industry, it is difficult to measure. The prupose of the research is to examine the affect of competitive advantage which consists of customer relationship, supplier relationship, intellectual property and fixed asset management on creating value for the manufacture companies using financial ratio analysis. This research using panel data to investigate 58 companies listed in Indonesia Stock Exchange (BEI) in the year 2008-2011. The results show that the relationship with suppliers, intellectual property and fixed asset management, can increase creating value for the manufacture companies that listed in BEI. Keywords: Competitive advantage, customer relationship, supplier relationship intellectual property,fixed asset management and creating value.